La comunicación institucional en la crisis del ébola en Europa: el caso de la crisis española de 2014 en sus inicios - Micaletto Belda, Juan Pablo; Gallardo Vera, Luis (IIRP, 2015)
This paper is based on the communicative actions which were taken by the Spanish Government because of the rise of Ebola virus in Spain the last October. Declarations from the Press conference were deeply analysed, as well as 36 messages published bynewspapers like El País and El Mundo as reactions to the Government ́s declarations. The main aim of the investigation was to get to know if the communicative strategy of this crisis was right during the first days. The original supposition was that the Government ́s communicative strategy was wrong because of the important mistakes produced by the Health Minister during the first Press conference. This hypothesis was finally confirmed.
The institutional communication on ebola crisis in Europe: the first moments of the 2014 spanish crisis
Keywords: Comunicación en las organizaciones; Gestión de crisis (Políticas públicas); Opinión Pública; Comunicación en crisis